A within-person investigation of recovery identity following substance use disorder: examining the impact of recovery-focused social contexts - Joseph H. Lancaster; Hannah B. Apsley; Timothy R. Brick; Timothy R. Brick; H. Harrington Cleveland (Frontiers in Public Health)
BackgroundThe social identity model of recovery (SIMOR) posits that adopting a recovery identity is vital for achieving favorable recovery outcomes. Until now, no studies have investigated recovery identity as a dynamic construct, although recent findings suggest it fluctuates from one day to the next. The present study examines the within-person association between recovery identity and sense of meaningfulness—an aspect of holistic recovery wellbeing. Because recovery-focused social contexts exist to support individuals’ recovery wellbeing, we assessed the moderating impact of two such contexts (recovery community centers [RCCs] and recovery meetings) as same-day moderators.Methods and materials91 RCC visitors across Pennsylvania completed daily diary surveys for 10 evenings. Daily measures of recovery identity, meaningfulness, recovery meeting and RCC attendance were analyzed in a multilevel Tobit model (to address right-censoring in the outcome data).ResultsResults indicated both day-level recovery identity (b = 0.79, SE = 0.04, p < 0.001) and person-level recovery identity (b = 0.94, SE = 0.11, p < 0.001) were positively associated with daily meaningfulness. Although the day-level interaction with RCC attendance was not significant (b = −0.11, SE = 0.14, p = n.s.), the interaction with recovery meeting attendance was (b = −0.27, SE = 0.13, p = 0.039), suggesting that meeting attendance buffered the effect of recovery identity on meaningfulness. A simple slopes analysis indicated that the relationship of recovery identity with meaningfulness was still statistically significant and positive in both cases (attended: b = 0.56, SE = 0.08, p < 0.001; not attended: b = 0.87, SE = 0.06, p < 0.001).ConclusionThese results suggest that people reporting stronger recovery identity also reported greater day-to-day meaningfulness. Further, on any given day for an individual, meaningfulness was higher on days recovery identity was stronger than usual for that individual, and lower on days when recovery identity was weaker. Meeting attendance reduced this effect, suggesting that meeting attendance may be especially helpful to recovery on days when recovery identity is low.